Genetic Type and Source Analysis of Natural Gas in the Leikoupo Formation of the Sichuan Basin in China - Qin, Shengfei; Zhang, Benjian; Huang, Chunhu; Li, Jiyuan; Wang, Jiamei; Tao, Gang; Zhou, Zheng (Frontiers in Earth Science, 2022)
The Middle Triassic Leikoupo Formation is largely extended through the Sichuan Basin, SW China. In this formation, several commercially exploited gas reservoirs have been discovered in western and central parts of the basin. Due to the complicated geochemical signatures of the natural gases in these reservoirs, there are contrasted interpretations about their sources, which hamper the evaluation and exploration for new gas resources in the area. To obtain complete understanding of the natural gas sources, the Leikoupo Formation gas reservoirs discovered so far in the Zhongba, Yuanba, Longgang, and Moxi gas fields were selected as the research object of this study. The genetic types and sources of the natural gases in the Leikoupo Formation are discussed based on gas geochemistry combined with their geological background. The natural gas in the top members of the Leikoupo Formation (T2l4 or T2l3) is partially originated from a humic kerogen contained in the source rocks from the overlying Upper Triassic Xujiahe Formation and from sapropel kerogen from the source rocks of the Leikoupo Formation itself. The natural gas of T2l1 member in the lower part of the Leikoupo Formation is mainly sapropel-type probably from the source rock of the Permian Wujiaping Formation, where the Permian Longtan Formation undergoes a phase change into the Wujiaping Formation The reversed δ13C1 and δ13C2 trend in the Leikoupo Formation of the Yuanba gas field is due to the more sapropelic source rocks and higher degree of maturity.